Resistive switching characteristics of ZnO-graphene quantum dots and their use as an active component of an organic memory cell with one diode-one resistor architecture - Ji, Yongsung; Lee, Sang-A; Cha, An-Na; Goh, Munju; Bae, Sukang; Lee, Sanghyun; Son, Dong Ick; Kim, Tae-Wook (ELSEVIER, 2015)
We investigated the resistive switching characteristics of a polystyrene:ZnO-graphene quantum dots system and its potential application in a one diode-one resistor architecture of an organic memory cell. The log-log I-V plot and the temperature-variable I-V measurements revealed that the switching mechanism in a low-current state is closely related to thermally activated transport. The turn-on process was induced by a space-charge-limited current mechanism resulted from the ZnO-graphene quantum dots acting as charge trap sites, and charge transfer through filamentary path. The memory device with a diode presented a similar to 10(3) I-ON/I-OFF ratio, stable endurance cycles (10(2) cycles) and retention times (10(4) s), and uniform cell-to-cell switching. The one diode-one resistor architecture can effectively reduce cross-talk issue and realize a cross bar array as large as similar to 3 kbit in the readout margin estimation. Furthermore, a specific word was encoded using the standard ASCII character code. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: DEVICES; FILMS; OXIDE; PERFORMANCE; INTEGRATION